Pediatric first aid, trauma knowledge, and attitude among parents and general population in Aseer region, Southern Saudi Arabia - Javed Iqbal Wani; Nouf Omar Almushayt; Wejdan Fuad Abbag; Lama Ali Buhran; Mir Nadeem (SAGE Open Medicine, 2022)
Objectives: Around the world, accidents and injuries are the leading causes of death among children. Because mothers and family members commonly administer first aid at home and at preschools, it’s critical to learn what parents and the public think about children’s mishaps. Our objective was to assess parents’ knowledge and attitude toward pediatric first aid in the Aseer region of Saudi Arabia. Methods: A cross-sectional study was conducted in the Aseer region of Saudi Arabia to assess the parents’ level of knowledge and attitude about pediatric first aid and trauma with an electronic- and paper-based multiple-choice self-administered questionnaire covering different medical emergencies. The Arabic and English versions of the questionnaire were made from the information obtained from the first aid educational content of the Saudi Ministry of Health. Results: When the participants were asked about their knowledge of pediatric first aid, arranged in descending order from most answers, 37% (n = 135) answered it was good, 30% (n = 111) answered that it was very good, 20% (n = 74) answered that it was not enough, and 13% (n = 47) answered that it was excellent. Results of the multiple linear regression analysis showed the knowledge score to be significantly higher among participants who had higher education levels (t = 2.039, p < 0.001), who had received first aid training before (t = 2.786, p = 0.0001), those who were already healthcare providers (t = 4.336, p < 0.001), those who were from rural districts (t = 2.5, p = 0.355), and younger personnel (t = 0.821, p = 0.345) The difference was not statistically significant. Conclusion: Although this study shows that the level of first aid knowledge among personnel who care for children was low, it also shows that they are interested in obtaining proper training.